Faktor Yang Mempengaruhi Minat Penggunaan Fitur Paylater di Aplikasi Shopee Pada Kalangan Mahasiswa Universitas Jember - Izza , Nurul; kartika; Pangesti , Resha Ayu Dwi (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2025)
Technology plays an important role in life, especially in the economic sector today. One of the technologies that is developing is electronic payment technology. Spaylater is an electronic-based payment that can make it easier for users to carry out transactions. This research aims to find out what factors in UTAUT 2 influence interest in using Spaylater among Jember University students as the Millennial generation. This research used a sample of Jember University students who had/are currently using Spaylater with a total sample of 100 respondents obtained via online (google form) and offline in the form of a questionnaire. Data processing using multiple linear regression analysis methods using the IBM SPSS26 program. The results of this research are that the factors Performance Expectations, Business Expectations, Social Influence, Facilitated Conditions, Hedonic Motivation and Price Value have no influence on interest in using Spaylater. Meanwhile, the Habit variable has an influence on Interest in Using Spaylater